Kendari Creative Hub with an Emphasis on Green Architecture - Nahdatunnisa, Nahdatunnisa; Tahir, M. Arzal; Mustafa, Abdul Fattah; Mislan, Soryanne (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Economic growth in the city of Kendari cannot be separated from the role of Small and Medium Enterprises (SMEs) which invoive creative economic actors scattered throughout the city. Creative industries that help support the economy consist of 16 sub-sectors namely Architecture, Applications and Game Development, Interior Design, Visual Communication Design, Product Design, Fashion, Photography, Crafts, Culinary, Music, Publishing, Advertising, Performing Arts, Fine Arts, Television and Radio, Film, Animation and Video. So we need a creative hub as a space for sharing, collaboration, commercial, production, etc. Which is a solution to respond to these problems and accommodate the activities of creative economy actors. The discussion method used is descriptive method, discussion of aspects related to the Creative Hub building facilities to architectural concepts with compilation study methods of primary data and secondary data. To design a centralized and integrated accommodation facility to accommodate creativity, as a space for sharing, collaboration, commercial, production, etc. and for the activities of creative economy actors. The application of green architecture into the planning of Kendari Creative Hub is applied to land efficiency, material utilization, which is easily available around the site, utilization of natural resources in lighting, ventilation and building energy sources, use of rainwater harvesting and recycling, especially in water use. With the application of green architecture into Kendari Creative Hub planning, it is hoped that it can be a solution in exploiting natural potential and minimizing the negative impact caused by moderation and efficiency in the use of building materials, energy, and development space on the natural environment.